Environmental and economic impacts assessment of concrete pavement brick and permeable brick production process - A case study in China. (10th January 2018) - Yuan, Xueliang; Tang, Yuzhou; Li, Yue; Wang, Qingsong; Zuo, Jian; Song, Zhanlong
Abstract: Permeable brick is used gradually with the promotion of sponge city development in China in recent years. It is imperative to thoroughly analyze the environmental and economic impacts of permeable brick compared to widely used concrete pavement brick. This paper analyzes and compares the environmental impact and economic cost impact of concrete brick and permeable brick in the system boundary of "cradle-to-gate", using the life cycle assessment approach. From the perspective of source tracking, the key processes and materials are identified for their significant environmental impacts. The results show that environmental impacts and economic cost of concrete pavement brick is lower if the water-saving potential of permeable brick during the service stage is not considered. The key materials with most significant environmental impact are basalt powder and cement for concrete pavement brick. By contrast, cement and crushed gravel are the key materials for permeable brick that caused the most environmental impacts. According to the process that each key material belongs to, the corresponding measures are proposed. Permeable brick in each function unit can form rain infiltration of 2.01 m 3 during the service stage. This would bring significant economic, environmental and social benefits in terms of groundwater conservation, fresh water saving, preventing urban waterlogging, cost savings of drainage system construction and maintenance, etc. The findings could provide useful reference for the development of sponge city and evidence-based policy making process. Graphical abstract: Highlights: LCA and LCC of permeable brick and concrete pavement brick. Key processes and key substances are identified by source tracking. Priority assigned for key processes by sensitivity analysis. "3R" principle is applied for key process optimization.